Outcomes and prognostic factors of fecal microbiota transplantation in patients with slow transit constipation: results from a prospective study with long-term follow-up. (8th November 2017) - Ding, Chao; Fan, Wenting; Gu, Lili; Tian, Hongliang; Ge, Xiaolong; Gong, Jianfeng; Nie, Yongzhan; Li, Ning
Abstract: Background and aim: Gut microbiota may contribute to regulate colonic motility, which is involved in the etiology of constipation. Fecal microbiota transplantation (FMT) has been demonstrated to restore intestinal homeostasis. The aim of this study was to evaluate the clinical outcomes and prognostic factors of FMT for the treatment of slow transit constipation (STC). Methods: Fifty-two patients with STC received standardized FMT and were followed up for 6 months. Bowel habit, colonic transit time, constipation-related symptoms (PAC-SYM score), quality of life (PAC-QOL score), treatment satisfaction scores and adverse events were monitored. The primary efficacy endpoint was the proportion of patients having on average three or more complete spontaneous bowel movements (CSBMs) per week. Results: The primary efficacy endpoint was achieved in 50.0%, 38.5% and 32.7% of patients over week intervals 3–4, 9–12 and 21–24, respectively ( P  < 0.01 for all comparisons). Significant improvements were also observed in other bowel movement assessments, colonic transit time, constipation-related symptoms and quality of life; but all improvements diminished at weeks 12 and 24. Incompleteness of evacuation served as the only factor associated with efficacy. No serious treatment-related adverse events were observed. Conclusion: This study suggested FMT was effective and safe for STC, while a late loss of efficacy was also observed. A lower degree of sensation of incompleteness predicted a better outcome.